2023
DOI: 10.2147/prbm.s399466
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Anxiety: Serial Mediation by Trust in the Government and Hope

Abstract: Purpose How to reduce the damage of COVID-19 pandemic to people’s mental health is a current research hotspot. The present study examined the mediating role of trust in the government and hope in the relationship between fear of COVID-19 and anxiety. Participants and Methods In this cross-sectional study, a total of 1053 Chinese subjects (20.24±3.97 years old, 85.3% female) were investigated by using the Fear of COVID-19 Scale, Anxiety Scale, Trust in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our finding that fear of COVID‐19 was associated with psychological distress corroborates those of previous studies showing the association between fear of COVID‐19 and psychological distress, such as depression and anxiety, in population with various backgrounds 31–34 . We also showed that fear of COVID‐19 caused work impairment, which was exerted entirely through psychological distress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that fear of COVID‐19 was associated with psychological distress corroborates those of previous studies showing the association between fear of COVID‐19 and psychological distress, such as depression and anxiety, in population with various backgrounds 31–34 . We also showed that fear of COVID‐19 caused work impairment, which was exerted entirely through psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…If citizens believe that the epidemic continues to develop and increase fear of COVID‐19, then they feel uncertain about the ability of their government to control the spread of the epidemic, resulting in government distrust and increased anxiety. This finding needs to be replicated in other countries, but might suggest the importance of governmental control measures of the virus and information provision 32 …”
Section: Discussionmentioning
confidence: 93%
“…Presumably, that effect may be explained by previous ndings, indicating that worry about life during pandemic was associated with low government policy trust [28], whereas worry about COVID-19 itself associated with high government trust and support of government anti-COVID-19 measures [29]. Trust in government, in turn, may ameliorate adverse mental conditions evoked by pandemic [30].…”
Section: Discussionmentioning
confidence: 98%
“…These uncertainties invariably heighten the likelihood of individuals experiencing anxiety. Thus, fear of COVID-19 emerges as a significant contributor to anxiety [ 16 ]. In the other study Jingjing Gao, mentioned that the COVID-19 pandemic was particularly challenging for those unemployed or with low income, as they bear a heavier financial burden due to restricted physical activity.…”
Section: Discussionmentioning
confidence: 99%